Theory Of Planned Behavior Implementation (Planned Behavior) In Mother Behavior In Postpartum Care In The House Of Mother's Children Fauziah Tulungagung - Biedasari Emi Chandra (Journal for Quality in Public Health, 2017)
Postpartum or puerperium begins 1 hour after birth of the placenta up to 6 weeks (42 days) afterwards. Parents, especially mothers, need to have the knowledge and readiness to conceive, give birth and breastfeed children. One of the factors that can cause maternal death is complications that occur during the puerperium. Postpartum complications of the highest incidence rate in Indonesia are bleeding and infection. This research is an observational analytic research with cross sectional approach. In the cross-sectional study, the researchers conducted observations or measurements of variables at one particular moment. Measurement of variables in one moment does not mean that all objects are observed exactly at the same time, but it means that each subject is observed only once and the measurement of the subject variable is performed during the examination. The results of research based on chi square test showed a significant influence that is attitude ρ = 0,18 where ρ > α (0,05) so that H0 accepted mean no attitude influence. The subjective norm ρ = 0.35> ρ > α (0,05) so that H0 is accepted which means there is no influence between subjective norms. Ability to control ρ = 0.12 > ρ > α (0,05) so that H0 is accepted which means there is no influence between the perception of control ability. Interest ρ = 0.96 > ρ > α (0.05) so that H0 is accepted which means there is no influence of interest. The most dominant fator is the education level, p = 0.03 > p < α (0.05) so that H0 is rejected which means there is an influence between the level of education in behavior on postpartum care at Rumah Sakit Ibu Anak Fauziah Tulungagung. The Health Service of Tulungagung through mother's hospital Fauziah is expected to socialize the community about postpartum care so that the public can express the problems especially the mothers without burdened by the existence of panisment such as influence in value and others.